Catatan Kehadiran Dosen Melalui Management System FO AO - Rifaatussalwa Hayati; Devi Puspita Sari; Gilang Kartika Hanum (UNIVERSITAS RAHARJA, 2024)
Recording the lecturer's attendance at each lecture is a routine that the lecturer must carry out at the start of the lecture. This is proof that a lecturer has carried out his teaching duties and is a determinant in several other matters such as remuneration and lecturer discipline in carrying out lectures. FO AO (Front Office Attendance Online) is one of the management systems implemented by Raharja University, designed with the aim of improving the quality of service information for admin lecturers, heads of study programs and leaders and making it easier for receptionists to operate the system in accordance with the SOP implemented by management. There have been many applications created in previous research regarding lecturer attendance records, including using Android and QR codes. This research was built with a different view using data collection methods and SWOT as a system analyst. The FO AO design implemented uses an analyst system, design system, constructions and testing implementation system. The results of testing that have been carried out show that the FO AO management system in this research can make it easier for officers to provide attendance services to lecturers as a record of their attendance at Raharja University and produce real-time digital information with good data validation